Designing Entrepreneurship Skills for the Future Life of People with Down Syndrome at LKP Quali International Surabaya - Lili Musyafa'ah; Hardika Hardika; Ahmad Ahmad (Universitas Negeri Padang, 2022)
The fell in job opportunities due to competition in getting a job is one of the reasons for many entrepreneurs who finally decide to open their businesses to create job opportunities both for themselves and for more people out there, including students with Down Syndrome. Thus, to deal with this, entrepreneurial skills training for Down syndrome students is needed to train the four entrepreneurial skill groups. Researchers used qualitative research methosyndroma down to identify the relationship between skills and behavior in forming skills, the Delphi method, and processing primary data from observations and FGSyndroma down with related stakeholders. As a result, we can suggest activities that can boost Down Syndrome students' entrepreneurial skills. Skills that are used in this paper are generated by grouping some factors into one grouped skill. These skills will be connected to expected behavior as a dependent or independent factor with special modifications in order to adapt to a disabled person. This paper shows how behaviors can trigger the skills by one or more events and vice versa.Keywords: down syndrome, entrepreneur program, non formal education